Teater Wayang Golek Topeng GEGER GIANYAR - Kertajaya, I Ketut; Sedana, I Nyoman; Sidia, I Made (Pusat Penerbitan LP2MPP ISI Bali, 2025)
This study presents the creation of Wayang Golek Topeng: Geger Gianyar, a theatrical innovation that reinterprets Balinese performing arts in response to contemporary cultural dynamics. Rooted in the dual challenge of preserving tradition while embracing modernity, the work employs wayang golek topeng as a hybrid medium that integrates the symbolic depth of Balinese topeng with the dramaturgy of rod puppetry. The creative process was guided by Prof. I Nyoman Sedana’s Catur Datu Kawya framework—Pandulame (imagination), Adicita-Adirasa (ideas and emotions), Sranasasmaya (media and method), and Gunatama (technical skills)—applied through collaborative practice with the Manduka Asrama Art Community in Gianyar. The work dramatizes social tensions and identity struggles in Gianyar, symbolizing broader cultural negotiations within Balinese society. Its novelty lies in the synthesis of mask-dance aesthetics and puppetry, producing a multisensorial performance that bridges sacred symbolism with contemporary stagecraft. Beyond its artistic value, the performance contributes to national discourse on cultural sustainability by positioning traditional puppetry as an adaptive medium for education, reflection, and intercultural dialogue. Thus, Geger Gianyar affirms the strategic role of practice-based research in revitalizing Indonesian performing arts while fostering cultural resilience in the era of globalization.